Fostering Critical Thinking in Arabic Language Learning: An Integrated Deep Learning–Love-Based Curriculum Approach - Manisha Aulia; M. Abdul Hamid; Nurhadi; Nur Kholis; Budi Santoso; Muhammad Hasyim (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study aims to analyze the implementation of the Deep Learning Approach integrated with the Love-Based Curriculum in Arabic language learning and its contribution to developing students’ critical thinking skills at MTsN Kota Batu. This study employed a descriptive qualitative approach to understand the learning process, classroom interactions, teachers’ experiences and students’ responses to the implementation of this integrative approach. Data were collected through observation, semi-structured interviews, documentation and students’ reflections. The data were then analyzed using Miles and Huberman’s interactive model, which consists of data reduction, data display and conclusion drawing. The findings indicate that the integration of the Deep Learning Approach in Arabic language learning through the theme عِيَادَةُ الْمَرْضَىٰ was able to create meaningful, mindful and joyful learning through discussion, dialogue, reading, role play, presentation and reflection activities. The Love-Based Curriculum was also concretely integrated through the values of Hubbullah, Hubburrasul, Hubbunnafs, Hubbunnaas, Hubbul Bi’ah and Hubbul Wathan, which were reflected in the habituation of prayer, the strengthening of manners, empathy, cooperation, environmental awareness and love for the homeland. The integration of these two approaches contributed to the development of students’ critical thinking skills through interpretation, analysis, evaluation, inference, explanation and self-regulation activities. This study concludes that Arabic language learning can be developed as an integrative space for language mastery, the internalization of Islamic values and the strengthening of critical thinking skills. The novelty of this study lies in its emphasis that the Deep Learning Approach and the Love-Based Curriculum not only improve the classroom learning atmosphere but also form a humanistic, reflective, contextual and relevant pedagogical approach that responds to the needs of Islamic education in the twenty-first century.